ҚОЖАҚАТ МИКРОӨСІМДІКТЕРІНДЕГІ IN VITRO ЖАҒДАЙЫНДА ҚАРҚЫНДЫ ӨСУ ЖƏНЕ ҚАРТАЮ ПРОЦЕСТЕРІНЕ ƏСЕР ЕТУШІ КЕЙБІР ФИЗИОЛОГИЯЛЫҚ КӨРСЕТКІШТЕРДІҢ ДИНАМИКАСЫ (Experimental biology, 2009)
Some biochemical parameters of blackberry microplants stored under long-term in vitro preservation at +5 °С have been analysed. It is established, that during the long-term in vitro preservation in conditions at +5 °С the content of an ascorbic acid in leaves of a blackberry is sharply reduced (in 25 times within 8 months of preservation). The content of free proline increases in the beginning of preservation, and then is reduced. Level of Н2О2 in leaves of the blackberry, stored long time at low temperature, does not vary within the first 4 months and then increases. Peroxidaseactivity increases in 4-8 months of preservation and is decreased by 12 month of preservation. It is concluded that the most probable reason of ageing and destruction of microplants in conditions of long-term in vitro preservation is ncrease of a Н2О2 level.
Keywords: biochemical; analys